Perceived stress and depressive symptoms not neuropsychiatric symptoms predict caregiver burden in Alzheimer’s disease: a cross-sectional study - Manee Pinyopornpanish; Kanokporn Pinyopornpanish; Atiwat Soontornpun; Surat Tanprawate; Angkana Nadsasarn; Nahathai Wongpakaran; Tinakon Wongpakaran (BMC Geriatrics, 2021)
Abstract Background Caregiver burden affects the caregiver’s health and is related to the quality of care received by patients. This study aimed to determine the extent to which caregivers feel burdened when caring for patients with Alzheimer’s Disease (AD) and to investigate the predictors for caregiving burden. Methods A cross-sectional study was conducted. One hundred two caregivers of patients with AD at Maharaj Nakorn Chiang Mai Hospital, a tertiary care hospital, were recruited. Assessment tools included the perceived stress scale (stress), PHQ-9 (depressive symptoms), Zarit Burden Interview-12 (burden), Clinical Dementia Rating (disease severity), Neuropsychiatric Inventory Questionnaires (neuropsychiatric symptoms), and Barthel Activities Daily Living Index (dependency). The mediation analysis model was used to determine any associations. Results A higher level of severity of neuropsychiatric symptoms (r = 0.37, p < 0.01), higher level of perceived stress (r = 0.57, p < 0.01), and higher level of depressive symptoms (r = 0.54, p < 0.01) were related to a higher level of caregiver burden. The direct effect of neuropsychiatric symptoms on caregiver burden was fully mediated by perceived stress and depressive symptoms (r = 0.13, p = 0.177), rendering an increase of 46% of variance in caregiver burden by this parallel mediation model. The significant indirect effect of neuropsychiatric symptoms by these two mediators was (r = 0.21, p = 0.001). Conclusion Caregiver burden is associated with patients’ neuropsychiatric symptoms indirectly through the caregiver’s depressive symptoms and perception of stress. Early detection and provision of appropriate interventions and skills to manage stress and depression could be useful in reducing and preventing caregiver burden.